2016
DOI: 10.1021/acs.jmedchem.6b01277
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Mycobacterium tuberculosis InhA Inhibitors by Binding Sites Comparison and Ligands Prediction

Abstract: Drug discovery is usually focused on a single protein target; in this process, existing compounds that bind to related proteins are often ignored. We describe ProBiS plugin, extension of our earlier ProBiS-ligands approach, which for a given protein structure allows prediction of its binding sites and, for each binding site, the ligands from similar binding sites in the Protein Data Bank. We developed a new database of precalculated binding site comparisons of about 290000 proteins to allow fast prediction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 72 publications
0
40
0
Order By: Relevance
“…Inverse molecular docking was performed with the fragment-based CANDOCK program [37], which was used to screen curcumin against all available human protein structures obtained from the Protein Data Bank (PDB) [38]. As blind docking was unfeasible due to the size of the PDB, we identified small molecule binding sites on the proteins and prepared them for inverse docking according to the procedure described in [39]. A binding site was defined as the space occupied by the union of one to several ligands that bind to similar binding sites and for which a co-crystal structure exists in the PDB.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inverse molecular docking was performed with the fragment-based CANDOCK program [37], which was used to screen curcumin against all available human protein structures obtained from the Protein Data Bank (PDB) [38]. As blind docking was unfeasible due to the size of the PDB, we identified small molecule binding sites on the proteins and prepared them for inverse docking according to the procedure described in [39]. A binding site was defined as the space occupied by the union of one to several ligands that bind to similar binding sites and for which a co-crystal structure exists in the PDB.…”
Section: Methodsmentioning
confidence: 99%
“…The docking search space was therefore focused on binding sites, which reduced the time complexity of the inverse docking. A previous version of this database was successfully used for discovery of small-molecule inhibitors of inhibin α (InhA) enzyme in Mycobacterium tuberculosis and this resulted in the identification of three previously unrecognized inhibitors with novel scaffolds [39].…”
Section: Methodsmentioning
confidence: 99%
“…455,456 Following up on these findings, Salentin et al used the Protein Data Bank, which contains structural data for more than one thousand different drug targets, to explore any drug-target pairs, which have similar interactions with BVDU and thymidine kinase. 457,458 The antimalarial drug amodiaquine was found to inhibit HSP27 chaperone function and reverse tumor drug resistance in multiple myeloma cell lines. Binding site comparisons are also a popular approach to predict similar pharmacological drugs.…”
Section: Technological Approaches To Drug Repurposing For Cancer Therapymentioning
confidence: 99%
“…Recently Joshi et al (2017) have used target to drug approach and shown that compounds such as pyrrolyl benzohydrazide derivatives inhibit InhA directly. Similarly Stular et al (2016) using molecular docking found three novel compounds that bind InhA. Biological testing confirmed that these compounds inhibit InhA.…”
Section: Discussionmentioning
confidence: 90%